Discovery of a New Intermediate Enables One‐Step Deposition of High‐Quality Perovskite Films via Solvent Engineering. Issue 4 (1st February 2021) - Hu, Chen; Shivarudraiah, Sunil B.; Sung, Herman H. Y.; Williams, Ian D.; Halpert, Jonathan E.; Yang, Shihe
Abstract : Bromide‐based organo‐metal halide perovskites have shown great potential for use in tandem solar cells (SCs), light‐emitting diodes (LEDs), and photodetectors. Herein, a new protocol using a one‐step deposition method for producing formamidinium lead bromide (FAPbBr3 ) perovskites is reported, which features a solvent‐engineered intermediate phase to achieve superior films. For the first time, a FABr–PbBr2 –DMSO intermediate is identified and single crystals of the same intermediate compound are synthesized. A systematic investigation of phase evolution in the film formation process reveals that DMSO enables crystallization of the FABr–PbBr2 –DMSO intermediate and thus modulates the crystallization process of FAPbBr3 perovskite, achieving uniform, smooth films with Volmer–Weber morphology. To prevent hole leakage arising from the larger bandgap of FAPbBr3 than FAPbI3, an additional layer of Mg‐doped ZnO nanoparticles is added. As a result, inverted SCs using these solvent engineered films achieve power conversion efficiencies (PCEs) of up to 9.06%, the highest reported efficiency for inverted FAPbBr3 perovskite devices. Abstract : A new intermediate FABr–PbBr2 –DMSO is discovered in early stage of perovskite spin‐coating. With this crystalline compound, the crystallization dynamics can be modulated to achieve controlled morphologies of FAPbBr3 films by simply varying the solvent composition. Mg–ZnO nanoparticles is introduced for wide bandgap perovskite solar device with an increased efficiency of over 9% based on inverted solar cell structure.